2017
DOI: 10.1038/srep39286
|View full text |Cite
|
Sign up to set email alerts
|

Weak functional connectivity in the human fetal brain prior to preterm birth

Abstract: It has been suggested that neurological problems more frequent in those born preterm are expressed prior to birth, but owing to technical limitations, this has been difficult to test in humans. We applied novel fetal resting-state functional MRI to measure brain function in 32 human fetuses in utero and found that systems-level neural functional connectivity was diminished in fetuses that would subsequently be born preterm. Neural connectivity was reduced in a left-hemisphere pre-language region, and the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 99 publications
1
106
0
Order By: Relevance
“…62 Furthermore, reduced neural connectivity was recently reported in fetuses exposed to chorioamnionitis before preterm birth. 63 Children born preterm without overt neonatal white matter injury had altered neural connectivity at 12 years of age compared to term born controls (assessed using diffusion tensor and volumetric MRI). 64 Follow-up to 16 years showed reduced cerebral microstructural integrity, and lower total white and grey matter volumes.…”
Section: Impaired Connectomics In the Infant Born Pretermmentioning
confidence: 99%
“…62 Furthermore, reduced neural connectivity was recently reported in fetuses exposed to chorioamnionitis before preterm birth. 63 Children born preterm without overt neonatal white matter injury had altered neural connectivity at 12 years of age compared to term born controls (assessed using diffusion tensor and volumetric MRI). 64 Follow-up to 16 years showed reduced cerebral microstructural integrity, and lower total white and grey matter volumes.…”
Section: Impaired Connectomics In the Infant Born Pretermmentioning
confidence: 99%
“…One study examined the relation between fetal eye-movements and fetal brain FC and found that fetal eye-movements were associated to simultaneous networks in visual- and frontal areas of the brain [32]. Very recently, the first study associated fetal FC to prematurity [33] – a relatively common negative birth outcome associated with many complications later in life (e.g., [34]). The authors compared fetal FC between fetuses that would subsequently be born preterm and normally developing fetuses and found that neural functional connectivity was diminished in fetuses that would subsequently be born preterm.…”
Section: Potential Of Fetal Fc Researchmentioning
confidence: 99%
“…The relationship between nodes and edges offers insight into the topological properties of functional organization and efficiency of brain networks (Sporns, Chialvo, Kaiser, & Hilgetag, 2004), with optimal communication in "small-world" networks, comprising both local segregation and global integration (Watts & Strogatz, 1998). GTA applied to resting-state functional magnetic resonance imaging (rs-fMRI) has been used to characterize the functional topography of the human brain from the fetal period through to adulthood (Bathelt, O'Reilly, Clayden, Cross, & De Haan, 2013;De Asis-Cruz, Bouyssi-Kobar, Evangelou, Vezina, & Limperopoulos, 2015;Gao et al, 2015;Thomason et al, 2017;van den Heuvel et al, 2018). Wen et al (2018) have shown that during the first year of life the modular organization of the brain functional network is progressively increasing and subdividing into an increasing number of functional modules together with stabilizing intramodular connection and clustering and intermodular connections.…”
mentioning
confidence: 99%